Business continuity management systems : implementation and certification to ISO 22301 - Estall, Hilary (BCS, The Chartered Institute for IT, 2012)
Annotation This practical guide is written for organisations who are implementing a business continuity management system and certification in line with ISO 22301. The development of a BCMS requires commitment, time, resourcefulness and management support. This book will fully equip those new to business continuity management or to management systems with survival skills for the ups and downs of the journey. Enriched with checklists, worksheets and invaluable top tips.
Keywords: Crisis management.; Emergency management.; Business planning.; elektronické knihy; electronic books